The Role of Legal Culture in Corruption Eradication Effort (A Comparative Study of Indonesian and Japanese Corruption Crime Handling) - Laely Wulandari; Lalu Parman (Unram Law Review, 2019)
In a comparative study of Eradicating Corruption in Indonesia and Japan appears that law culture plays a significant role. Indonesia has special institution that deals with corruption while Japan does not have it. Nevertheless, cases of corruption in Indonesia are higher than in Japan. This is due to the Indonesian culture of ewuh pakewuh, reluctant, and has two different views in dealing with corruption. On the one hand, Indonesia rejects corruption, but on the other hand, it commits actions that support corruption. Meanwhile, Japan has a strong culture of shame for committing law violations both at the community level and law enforcement officers.